Effect of Rural Culture on Food Choices of Person Diagnosed with Heart Failure - Dickinson, Mary Beth (My University, 2010)
Five million people in the United States have heart failure. Different life styles and availability of food may have an impact on the recommended two gram sodium diet for persons with heart failure. The objective of this study is to investigate the shopping habits, cooking, social activity with eating, and food sources from hunting, fishing, and garden foods of people with heart failure who lives in rural areas. The study will examine food consumption at public places as church banquets, senior centers, restaurants, fast food restaurants, and at family/friends' homes.
Color poster with text, images, and graphs.
Keywords: Food habits--Sociological aspects; Heart failure--Patients--Social life and customs; Country life--Health aspects; Posters